Validating Health Literacy and Numeracy Measures in Minority Groups - Rosette J. Chakkalakal; Sneha Venkatraman; Richard O. White; Sunil Kripalani; Russell Rothman; Kenneth Wallston (SLACK Incorporated, 2017)
Background: Validation studies of existing health literacy or numeracy tools among racial/ethnic minorities are limited. Objective: This study assessed the validity of the Subjective Numeracy Scale (SNS), the Diabetes Numeracy Test (DNT-5), the Brief Health Literacy Screen (BHLS), and the Short Test of Functional Health Literacy in Adults (S-TOFHLA) by trait (health literacy or numeracy) and by method (subjective or objective) among non-Hispanic white (NHW), non-Hispanic black (NHB), and Hispanic patients with type 2 diabetes mellitus (T2DM). Methods: We conducted a secondary analysis of baseline data from the Partnering to Improve Diabetes Education (PRIDE) study, a clustered randomized controlled trial testing the efficacy of a health communication intervention on T2DM outcomes at state Department of Health clinics in middle Tennessee. PRIDE participants with race/ethnicity data available (n = 398) were included in this study. Most patients identified as NHW (59%), 18% identified as NHB, and 23% identified as Hispanic. Pearson correlations among the 4 measures were compared for each racial/ethnic group by trait and method. The convergent validity of each measure with education was also assessed using Pearson correlation analyses. Key Results: Significant correlations were observed across all 3 subgroups for the numeracy measures (SNS and DNT-5) and the objective measures (DNT-5 and S-TOFHLA). Nonsignificant correlations were observed among Hispanic participants for the health literacy measures (BHLS and S-TOFHLA, correlation coefficient = 0.13) and among NHB and Hispanic participants for the subjective measures (SNS and BHLS, correlations coefficients = 0.15 and 0.09, respectively). A significant positive correlation was noted between education and each measure across all 3 subgroups. Conclusions: Subjective and health literacy measures demonstrate weaker correlations than objective and numeracy measures, respectively, among minority patients in this study. Our findings highlight the need to further evaluate the appropriateness of these tools for use with minority populations, particularly the BHLS for Hispanic patients.